Application and challenges of tumor organoid technology in precision immunotherapy - Zhao, Xiaoming; Gao, Jun; Liu, Yinan; Shi, Yawen; Zhang, Meng; Zhang, Chen; Chen, Jinghong (Frontiers in Immunology, 2025)
In recent years, tumor organoid technology has emerged as a crucial bridge connecting basic research and clinical applications with a deeper understanding of tumor biology. This technology enables reconstruction of tumor-native structures in vitro and their microenvironments, providing new possibilities for assessing individual responses and optimizing treatment strategies. This paper details the application prospects of organoid technology in tumor immune microenvironment reconstruction, personalized therapy, and drug screening. It also analyzes the current challenges faced by organoid technology in clinical translation, including model standardization, the integrity of immune microenvironment reconstruction, and the importance of interdisciplinary collaboration. Furthermore, we discuss how emerging technologies, such as 3D bioprinting and microfluidic chips, are driving advancements in tumor research. In the future, tumor organoid technology will used to support precision immunotherapy by establishing standardized processes and databases to enhance data comparability and reproducibility. creating a closed-loop system of “patient-organoid-multi-omics data-clinical decision support” will further promote the development of precision medicine and facilitate clinical application.